Analysis of Village Official' Competence, Organizational Commitment, and Transparency Towards Accountability of Village Fund with Mediation of Management and the Performance of the Village Government (Empirical Study of Village Government in Kuok District - Suarni Norawati; Alkudri Alkudri (Komunitas Dosen Indonesia, 2023)
This research aims to examine and investigation the effect of the village official competence, the organizational commitment of the village government, and also transparency on the accountability of village fund management through the performance of the village government. The sample study all village official in Kuok District, Kampar Regency, totaling 83 respondents. The data analysis method uses descriptive statistical analysis and the data analysis tool uses Smart PLS. The research results show that the competence of village official has a significant effect on the performance of the village government, organizational commitment has a significant effect on the performance of the village government, transparency in village financial management has no significant effect on the performance of the village government. Village government performance has a significant effect on the accountability of village financial management, competence has a significant effect on accountability of village financial management, organizational commitment has significant effect on accountability of village financial management, and transparency has no significant on accountability of village financial management. Competence has a significant effect on the accountability of village financial management through the performance of the village government